MAKNA KARIER AKUNTAN PUBLIK BAGI MAHASISWA AKUNTANSI - Shafirah Nur Faiqah Olola; Tenriwaru Tenriwaru; Subhan Subhan (Magister Akuntansi, Universitas Atma Jaya Makassar, 2020)
The purposes of this research is to know what is the meaning of public accountant career for accounting student and to know how ideological view towards career election as public accountant. This research uses qualitative approach with interpretive paradigm and informant used on this research is accounting student on ideological-based university at Makassar. Primary data is used for this research with observing and direct interview with the informants. Data analysis method used is data reduction, data display, data classification, data verifying, and draw final conclusion from the research results. The research result shows that accounting student interpret the public accountant profession as a challenging profession, promising in financial terms (salary), has promising employment field, has important influence and big responsibility, also is a risky job.